Failure to recognize Low non-treponemal titer syphilis infections in pregnancy May lead to widespread under-treatment - Swayze, Emma Jane (2021)
Objectives: Rates of maternal syphilis have increased five-fold in Brazil in the past decade. While penicillin remains the only appropriate treatment for maternal syphilis, we hypothesized that low non-treponemal titers (<1:16) may lead to reduced penicillin treatment in Brazil. Methods: Using Brazilian Ministry of Health data on women diagnosed with maternal syphilis between January 1, 2010, and December 31, 2018, we conducted a random-effects logistic regression model with a cluster correction at the state level to evaluate predictive factors of penicillin treatment. Results: We observed yearly increases in cases of pregnant women with syphilis from 2010 to 2018. There was significant variation by state: 52,451 cases were reported in São Paulo, followed by 26,838 in Rio de Janeiro. Among 215,937 cases of maternal syphilis, 91·3% received penicillin. In the random-effects model, a non-treponemal titer ≥1:16 was associated with 1·44 higher odds of receiving penicillin (95% confidence interval [CI]: 1·391·48), and prenatal care was associated with a 2·12 increased odds of receiving penicillin (95% CI: 2·022·21). Although there is an association between the absence of prenatal care and inadequate treatment for syphilis, 83·2% of women in this cohort who did not receive penicillin were engaged in prenatal care. Conclusions: Providers may inappropriately exclude low non-treponemal titers and thereby fail to use penicillin treatment in maternal syphilis. While the cause of the maternal syphilis epidemic in Brazil is multifactorial, we believe our findings can be used to develop targeted interventions throughout Brazil as well as shape public health initiatives globally.